DEVELOPING ENGLISH RESEARCH ARTICLE WRITING GUIDE TEXTBOOK FOR NON-ENGLISH DEPARTMENT STUDENTS USING THE ADDIE MODEL - Isry Laila Syathroh; Siska Rizkiani (University of Kuningan, 2023)
This study aims to develop a textbook as a guide for writing research articles in English to answer the challenges faced by non-English department students in writing research articles in English. This research applies the R&D (Research and Development) method. The development of this textbook uses the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. In this study, data is collected through questionnaires and interviews. The questionnaires are delivered to 240 students in the non-English department, and interviews are administered with two lecturers at a private higher education institution. A textbook titled